What matters is when you play: Investigating the relationship between online video games addiction and time spent playing over specific day phases. (December 2018) - Triberti, Stefano; Milani, Luca; Villani, Daniela; Grumi, Serena; Peracchia, Sara; Curcio, Giuseppe; Riva, Giuseppe
Abstract: Online video gaming is now widely considered an activity possibly related to addictive behaviors, so that the diagnosis of Internet Gaming Disorder (IGD) is now included both in DSM-5 and ICD-11; however, there is still debate about some specific features of such disorder. One debated aspect is time spent playing: IGD gamers certainly play a high amount of time, but, on the other hand, also highly-engaged individuals or people working with video games (e.g.: eSports professional players) may play a lot without developing IGD. The literature agrees on the importance of deepening the role of time spent playing video games in IGD, to understand if it can be considered a symptom useful for the diagnosis, or not: one possibility is that time spent playing is not important in an absolute sense, but relatively to specific day phases. The present research involved 133 participants to test the relationship between average time spent playing over day phases (morning, afternoon, night; week, weekend days), age, game preferences and IGD. IGD score positively predicted time spent playing during weekend mornings, which are a day phase usually dedicated to other activities. Instead, time spent playing during afternoon was negatively predicted by age, according to this day phase being more related to youngsters' spare time, while night playing was related to preference for game genres which need dedicated time to organize multi-playing. Discussion deals with the utility of these preliminary results for future, more systematic research on IGD and its distinctive symptoms. Highlights: To investigate the role of time spent playing video games in problematic gaming Time spent playing may be important as associated to specific day phases. Problematic gaming predicts time spent playing video games during mornings. Time spent playing over other day phases is related to game preference and age.